Cotton in the Global Context : Discussion Paper for the Governments of Uzbekistan and Tajikistan - World Bank (Washington, DC, 2016)
Production in 2004 was actually running higher than consumption prior to 1995 and this has caused the existence of a world surplus of baled cotton in the form of stocks in warehouse. It is the existence of these “ending stocks” that has a large effect on the international price of cotton. Consumption began to outpace production in 2001 to 2003 period and this, mixed with crop disasters in various regions, caused the international price to rise. The reaction from many countries was to increase production in reaction to this. Cconsumption failed to match this increase in production, causing a fall in prices and a renewal of the world’s ending stocks.